Financing Municipal Energy Efficiency Projects - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2015)
Improving the energy efficiency (EE) of municipally owned buildings, such as schools and hospitals, and municipal infrastructure, such as public lighting, water supply, and district heating, offers budgetary savings on energy bills and a wide range of environmental and socioeconomic benefits. But relatively few municipal EE projects have been developed and implemented successfully. The challenges that limit EE investments in municipal buildings and facilities can be grouped into three broad areas: (i) a lack of awareness and incentives; (ii) insufficient implementation capacity; and (iii) limited access to financing. All three sets of challenges need to be addressed to scale up successful implementation of municipal EE projects. This Guidance Note focuses on the key issues faced by municipalities in accessing financing for EE investments, particularly for projects in the following four areas: indoor lighting, building retrofits, public lighting, and municipal utilities. The guidance note discusses the following potential financing mechanisms that can be used by municipalities to finance EE measures: budget financing, Funds developed specifically to address energy efficiency, public support to leverage commercial financing, and commercial financing.